Za yedinyy boyevoy proletarskiy front molodezhi - Kochergin, Nikolai Mikhailovich (1933)
Assembled on left side are a fascist, a capitalist, and artillery. Facing them, assembled on the right are armed people of different nationalities and red flags unfurled Original title: За единный бойёвый пролетарский фронт молодежи. Suggested translation: For the united militant proletarian youth front PO-0009